Communitas: Liturgy and Identity - Carvalhaes, Cláudio (International review of mission, 2011)
As many churches express concern about dwindling resources and even survival, they are simultaneously being confronted by the presence and needs of immigrants. Though often confessionally identified with the receiving congregations, immigrants pose specific challenges, the key to which is, perhaps unexpectedly, liturgy. Liturgical openness to a variety of worship ways facilitates new and necessary changes in power structure, mission thinking beyond mere multiculturalism, and new forms of community and discipleship.